ANALISIS PENGARUH HUTANG, EPS, ARUS KAS BEBAS, DAN PENINGKATAN ASET TERHADAP CASH DIVIDEND PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - SIREGAR B11110045, ASI MARYATI (Jurnal Manajemen Update, 2014)
Research that was conducted in the making of this thesis aimed to find out whether the independent variable that are; debt, Earning Per Share (EPS), free cash flow, and the increasing of assets, have significant influence toward their depended variable; cash divinded. The kind of research for this research is literary study. In this case, the object of the research is some manufacturing companies that were listed in Bursa Efek Indonesia (BEI) in 2009 till 2013 that being chosen based on specific criteria.Thedata used is the secondary data obtained from the financial report of manufacturing company in Bursa Efek Indonesia from Indonesian Capital Market Directory (ICMD). The analysis was being carried out using quantitative method. Quantitative method applied by using statistic technique by processing the datas in order to prove the proposed research hypothesis and analysis tools used by using multiple linear regression method. As the result of the research, it can be concluded that the variable debt, Earning Per Share(EPS) dan the free cash flow does not have any significant influence to cash dividend. While the increasing of assets does have significant influence to cash dividend. Key words:  Debt, Earning Per Share (EPS), free cash flow, increase in assets and Cash Dividend.